Global and Specific Cortical Volume Asymmetries in Individuals With Psychosis Risk Syndrome and Schizophrenia: A Mixed Cross-sectional and Longitudinal Perspective. (18th October 2019) - Damme, Katherine S F; Vargas, Teresa; Calhoun, Vince; Turner, Jessica; Mittal, Vijay A
Abstract: Cortical volumetric asymmetry (CVA) has been widely observed in individuals with psychosis, and is associated with etiological risk factors (e.g., genetics, neuromaturation) and treatment response. However, it is unclear whether CVA abnormalities emerge before psychotic illness onset. Understanding whether CVA manifests in clinical high-risk (CHR)—compared with healthy controls and schizophrenia patients (SCZ)—over time may inform our understanding of pathogenic factors. A total of 233 individuals: 73 CHR, 112 healthy controls, and 48 SCZ underwent an MRI and clinical interviews. Ninety-four individuals including healthy volunteers (HV) ( n = 49) and CHR ( n = 45), completed another scan at 12-months. CVA was compared by lobe in a repeated-measure design across groups, then nested by time in a longitudinal model. CHR and SCZ groups showed reduced global CVA compared with the healthy control groups but the CHR and SCZ group did not differ from each other. A group by lobe interaction indicated the presence of lobe specific reductions in frontal and cingulate CVA. Cingulate CVA was reduced in CHR and SCZ groups compared to HC groups but did not differ from each other. Frontal CVA was reduced in the older healthy controls compared with younger-HC and CHR, but did not differ from the similarly aged SZ group. CVA is similarly impacted in SCZ and CHR groups, potentially reflecting pathogenic processes. Longitudinal analyses provided further support for the neurodevelopmental hypothesis as CHR exhibited longitudinal changes in opposite directions from normative neuromaturation in HV, which was related to increasing risk for psychosis in the CHR.